Advances in rapid identification and susceptibility testing of bacteria in the clinical microbiology laboratory: implications for patient care and antimicrobial stewardship programs - Florian P. Maurer; Martin Christner; Moritz Hentschke; Holger Rohde (MDPI AG, 2017)
Early availability of information on bacterial pathogens and their antimicrobial susceptibility is of key importance for the management of infectious diseases patients. Currently, using traditional approaches, it usually takes at least 48 hours for identification and susceptibility testing of bacterial pathogens. Therefore, the slowness of diagnostic procedures drives prolongation of empiric, potentially inappropriate, antibacterial therapies. Over the last couple of years, the improvement of available techniques (e.g. for susceptibility testing, DNA amplification assays), and introduction of novel technologies (e.g. MALDI-TOF) has fundamentally changed approaches towards pathogen identification and characterization. Importantly, these techniques offer increased diagnostic resolution while at the same time shorten the time-to-result, and are thus of obvious importance for antimicrobial stewardship. In this review, we will discuss recent advances in medical microbiology with special emphasis on the impact of novel techniques on antimicrobial stewardship programs.